PENGARUH GOOD CORPORATE GOVERNANCE (GCG) DAN PENGUNGKAPAN LAPORAN KEUANGAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Firdah, Ila (Jurnal Riset Mahasiswa Akuntansi, 2014)
Value of the company is the information needed by investors in making decision. Every company is trying to do Good Corporate Governance is the implementation of Good Corporate Governance (GCG) to improve the performance of the company. This study aims to analyze the influence of Good Corporate Governance (GCG) and financial statement disclosure on firm value. The data used in this study is a secondary data extracted from the financial statements of manufacturing in Indonesia Stock Exchange listings are based purposive sampling with the period 2010-2012. The variables used are of Good Corporate Governance (GCG) and financial statement disclosure as independent variables and the dependent variable value as a company. The analysis technique used is multiple linear regression with a dummy variable for financial statement disclosure and classical assumption. Hyphotesis testing using t-test for analysis of the effect and the partial F test for analysis of the effects simultaneously. The results of this study of Good Corporate Governance (GCG) which is proxied by leverage and disclosure of financial statements in partial significant positive effect on firm value. While simultaneously Good Corporate Governance (GCG) and the disclosure of financial statements significant effect on firm value.